Criterion-Referenced and Norm-Referenced Assessment: An Analysis of Score Processing Techniques in Islamic Religious Education - Ikhwan Al Hafiz; Remiswal Remiswal; Khadijah Khadijah (Journal of Contemporary Pedagogy and Learning Science, 2026)
This study examines the conceptual foundations of Criterion-Referenced Assessment (CRA) and Norm-Referenced Assessment (NRA), with particular emphasis on their score-processing techniques and pedagogical relevance in Islamic Religious Education (IRE). A qualitative, non-empirical approach employing library research was adopted by systematically reviewing scholarly books, peer-reviewed journal articles, and relevant educational policy documents. The collected literature was analyzed through qualitative content analysis and comparative conceptual analysis to identify the characteristics, differences, pedagogical functions, and implications of both assessment approaches. The findings reveal that CRA evaluates students' achievement against predetermined competency standards, enabling objective interpretation of learning outcomes and supporting mastery learning through competency-based assessment. In contrast, NRA interprets achievement relative to group performance, making it more appropriate for ranking, classification, and selection purposes than for measuring competency attainment. The analysis further demonstrates that CRA is more compatible with the objectives of Islamic Religious Education because it facilitates comprehensive assessment across cognitive, affective, and psychomotor domains while supporting individualized feedback and competency development. Although NRA remains useful in specific educational contexts, its role in routine classroom assessment is complementary rather than primary. The study contributes to contemporary pedagogy by proposing an integrated conceptual perspective linking assessment paradigms, score-processing techniques, and competency-based evaluation in Islamic Religious Education.